The Limits of Marketplace Fee Discrimination - Mark J. Tremblay (Center for Economic Studies and ifo Institute (CESifo), 2021)
Platforms often use fee discrimination within their marketplace (e.g., Amazon, eBay, and Uber specify a variety of merchant fees). To better understand the impact of marketplace fee discrimination, we develop a model that allows us to determine equilibrium fee and category decisions that depend on the extent of fee discrimination available to the platform and we highlight how our fee discrimination strategies can be derived in practice using data from airbnb.com. In addition, we find that greater fee discrimination allows the platform to serve more markets in its marketplace but also increases fees in high surplus markets. However, if the platform enters into retail, then the platform reduces its fees and generates greater retail competition. These effects mitigate distortions from fee discrimination and improve welfare. In terms of policy, we show that (1) banning fee discrimination and platform entry is detrimental to welfare, (2) a vertical merger within a retail market mitigates fee distortions but is often worse than an equilibrium with platform entry into retail, and (3) taxing the platform in retail (not merchants) levels the retail playing field and can generate a Pareto improvement upon a policy that bans platform retail entry.
Keywords: L11; L12; L40; H21; L50; 330; platforms; platform retail entry; price discrimination; vertical integration; intermediary